KARAKTERISTIK HASIL PEMERIKSAAN IGM ANTI SALMONELA TYPHI DI LABORATORIUM SURYA HUSADHA DENPASAR PADA BULAN JUNI -NOVEMBER 2013 - Widyaningrat, Sagung Novita; Lestari, A.A. Wiradewi; Yasa, I Wayan Putu Sutirta (E-Jurnal Medika Udayana; vol 4 no 11(2015):e-jurnal medika udayana, 2015)
CHARACTERISTIC S EXAMINATION RESULTS IGM ANTI- SALMONELLA TYPHI IN LABORATORIUM SURYA HUSAD H A HOSPITAL DENPASAR ON JUNE UNTIL NOVEMBER 2013 Typhoid fever had been a global health problem, especially in developing tropical countries which have a bad hygienity. Indonesia is one of them that have high rate  incidents of typhoid fever (358-810/100,000 population). Typhoid fever is an acute infection caused by the bacterium Salmonella typhi . The bacterial inserted into the body through contaminated food by S. typhi and infecting the gastrointestinal tract. Tubex test is one of serological test, which often used to aid in the diagnosis of typhoid fever. Tubex test is a simple agglutination test which able to detect the establishment of IgM. This research described characteristics of the examination results in patients with typhoid fever using Tubex test at RS Surya Husadha laboratory in June until November 2013. Research methode that used is cross sectional, non-experimental with the data had taken  retrospective from the RS Surya Husadha Laboratory. 502 of patients that doing test tubex, 76 patient ( 15.1 % ) the result negative, 151 patient ( 30.1 % ), the results borderline and 275 patient ( 54.8 %) the result is positive. From gender characteristic, there was no significant difference which one more test tubex between men and women. But from the age group characteristic, the adult age group showed a higher positive results (30.5%).
Keywords: Tyfoid Fever, Tubex Test, Tubex Test prevalence